Consistent Estimation of the Impact of Tax Deductibility on the Level of Charitable Contributions - Reece, William S.; Zieschang, Kimberly D. (Econometrica, 1985)
When charitable contributions are tax deductible, the marginal price of charitable giving in other consumption foregone per dollar of contributions is generally less than unity. Further, if the income tax schedule is a progressive step function, the marginal price of contributions is generally a rising step function of the level of contributions. The problem of estimating a contributions demand function for individuals is therefore complicated by the spurious correlation between the level of contributions and the observed marginal price. We take this econometric problem into account in estimating a contributions demand function using data from the 1972-73 Consumer Expenditure Survey. After comparing our results with those of estimation techniques used by other authors, we provide evidence on the impacts of alternative tax policies on charitable giving using our estimates of the model parameters.